PENGARUH LIVE STREAMING, SHOPPING LIFESTYLE, PRICE DISCOUNT DAN FLASH SALE TERHADAP IMPULSE BUYING BEHAVIOR (Studi Empiris pada Konsumen Shopee) - Nurdiyanti, Emilia; Hidayati, Luk Luk Atul; Utami, Pranita Siska (Borobudur Management Review, 2025)
This study aims to determine the effect of Live Streaming, Shopping Lifestyle, Price Discount and Flash Sale on Impulse Buying Behavior. The sample used in this study were people who had made online purchases through Shopee. The sampling method in this study was accidental sampling with a sample size of 100 respondents. The analytical tool used is multiple linear regression with the help of SPSS 25 software. The results of the F test show that Live Streaming, Shopping Lifestyle, Price Discount and Flash Sale have a positive and simultaneous effect on Impulse Buying Behavior. The results of the t test show that Shopping Lifestyle has a positive effect on Impulse Buying Behavior, while Live Streaming, Price Discount and Flash Sale have no effect on Impulse Buying Behavior. Keywords: Live Streaming, Shopping Lifestyle, Price Discount, Flash Sale, Impulse Buying Behavior